Visualization and clinical relevance of the endolymphatic duct and sac in Ménière's disease - de Pont, Lisa M. H.; Houben, Maartje T. P. M.; Verhagen, Thijs O.; Verbist, Berit M.; Buchem, Mark A. van; Bommeljé, Claire C.; Blom, Henk M.; Hammer, Sebastiaan (Frontiers in Neurology, 2023)
Background: Ménière's disease (MD) is a chronic inner ear disorder with a multifactorial etiology. Decreased visualization of the endolymphatic duct (ED) and sac (ES) is thought to be associated with MD, though controversy exists whether this finding is specific for MD.Recent literature has revealed that two distinct ES pathologies, developmental hypoplasia and epithelial degeneration, can be distinguished in MD by using the angular trajectory of the vestibular aqueduct or ED-ES system (ATVA) as a radiographic surrogate marker. It has been suggested that these two subtypes are associated with distinct phenotypical features.However, the clinical differences between the ATVA subtypes require further validation.Research objective: to investigate whether (1) non-visualization of the ED-ES system is a discriminative radiological feature for MD in a cohort of vertigo-associated pathologies (VAP), and if (2) different angular trajectories of the ED-ES system in MD are associated with distinguishable clinical features.